Three-Tier Prognostic Index in Young Adults With Advanced Gastric Cancer - Chen, Guang-Liang; Huang, Yan; Zhang, Wen; Pan, Xu; Feng, Wan-Jing; Zhao, Xiao-Ying; Zhu, Xiao-Dong; Li, Wen-Hua; Huang, Mingzhu; Chen, Zhi-Yu; Guo, Wei-Jian (Frontiers in Oncology, 2021)
Purpose: To characterize clinical features and identify baseline prognostic factors for survival in young adults with advanced gastric cancer (YAAGC). Materials and Methods: A total of 220 young inpatients (refer to less or equal to 40 year-old) with an initial diagnosis of advanced gastric cancer were retrospectively enrolled in this study. Results: Of a consecutive cohort of 220 patients with YAAGC, the median overall survival (OS) time was 16.3 months. One-year survival rate was 43.6% (95% CI: 36.5 to 50.7). In this cohort, a female (71.4%, n=157) predominance and a number of patients with poorly differentiated tumors (95.9%, n=211) were observed. In the univariate analysis, OS was significantly associated with neutrophil-lymphocyte ratio (NLR) (≥ 3.12), hypoproteinemia (< 40g/L), presence of peritoneal or bone metastases, and previous gastrectomy of primary tumor or radical gastrectomy. In multivariate Cox regression analysis, hypoproteinemia (hazard ratio (HR) 1.522, 95%CI 1.085 to 2.137, p=0.015) and high NLR level (HR 1.446, 95%CI 1.022 to 2.047, p=0.021) were two independent poor prognostic factors, while previous radical gastrectomy was associated with a favorable OS (HR 0.345, 95%CI 0.205 to 0.583, p=0.000). A three-tier prognostic index was constructed dividing patients into good, intermediate or poor risk groups. Median OS for good, intermediate, and poor risk groups were 36.43, 17.87, and 11.27 months, respectively. Conclusions: Three prognostic factors were identified and a three-tier prognostic index was devised. The reported prognostic index may aid clinical decision-making, patient risk stratification, and planning of future clinical studies on YAAGC.